MEDIA LITERACY AS THE 21ST CENTURY SKILL - L. Petryk (Borys Grinchenko Kyiv Metropolitan University, 2017)
The paper is based on the 21st century skills that are an integral part in successful individual's training and professional activity in the era of the information society. Among them knowledge of core subjects, learning and innovation skills, information, media and technology skills, life and career skills are highlighted. It is determined that all the skills can't be formed separately from one another because all of them are interrelated and build a complex of skills to make a young person successful in life. Media literacy is singled out as a key 21st century skill by the author because its formation is conceptual in the contemporary educational process. Media literacy is defined as a set of motives, knowledge, skills and capacities that encourage media audience to search, experiment, use, analyze critically, evaluate, create and transfer media texts of different forms and genres. Media literacy is closely associated with the formation of critical and creative skills, media education, involvement in the partnership and active citizenship. The paper highlights the set of new media skills (play, performance, simulation, appropriation, multitasking, distributed cognition, collective intelligence, judgment, transmedia navigation, networking, negotiation, vizualization) that can be formed with the help of new media tools the use of which is the demand of modernity. These tools motivate a personality to active life in a globalized world. A four-level SAMR model is considered to be efficient to be integrated into educational process as it shows clearly how media tools can be used in teaching different subjects, in particular foreign languages. This model may be helpful to set objectives of the class, choose a right media tool or resource and the way of its use. Thus, media tools are able to turn a passive media consumer into active one and possess a set of the 21st century skills.